2013
DOI: 10.1063/1.4789412
|View full text |Cite
|
Sign up to set email alerts
|

Direct shape control of photoreduced nanostructures on proton exchanged ferroelectric templates

Abstract: Photoreduction on a periodically proton exchanged ferroelectric crystal leads to the formation of periodic metallic nanostructures on the surface. By varying the depth of the proton exchange (PE) from 0.59 to 3.10 μm in congruent lithium niobate crystals, the width of the lateral diffusion region formed by protons diffusing under the mask layer can be controlled. The resulting deposition occurs in the PE region with the shallowest PE depth and preferentially in the lateral diffusion region for greater PE depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
(42 reference statements)
5
17
0
Order By: Relevance
“…22 We have previously reported D PE z ¼ 0.084 6 0.004 lm 2 /h for congruent LN processed with the same PE conditions. 25 Thus, the MgO doping lowered the PE diffusion rate in the z-direction, consistent with the findings of Ref. 27.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…22 We have previously reported D PE z ¼ 0.084 6 0.004 lm 2 /h for congruent LN processed with the same PE conditions. 25 Thus, the MgO doping lowered the PE diffusion rate in the z-direction, consistent with the findings of Ref. 27.…”
supporting
confidence: 81%
“…22 Both aforementioned approaches (poling and PE) can be used to fabricate periodic arrays of either reversed ferroelectric domains or polarization-reduced regions across the crystal surface. Recently, we demonstrated that such periodic PE:LN templates 23,24 can be used to form arrays of Ag nanostructures 1,3 and that the width and height of the nanostructures can be controlled by the PE depth 25 and AgNO 3 concentration, 26 respectively. A technique commonly employed to reduce the sensitivity of LN crystals to the photorefractive effect (i.e., optical damage) is MgO doping, 27 which also influences the PE process.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Due to its good nonlinear optical properties and high resistance to photorefraction, 11,12 highly Mg doped LN (Mg:LN) has gained significant interest for applications in optics as quasi phase matched devices. [13][14][15] Ferroelectric properties of LN change upon Mg doping and in numerous poling experiments 13,[15][16][17] lower coercive fields and longer stabilization times for freshly poled domains 15,18,19 have been observed, as well as unidirectional high conductivity states 15,19 that were ascribed to charged domain walls.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the substrate is oriented in the þz direction, the positive charge carriers move in the opposite direction, towards the PE area, causing currents to be confined at the inside edge of the PE area. These lateral fields also reportedly play an important role in photodeposition experiments where photogenerated electrons can accumulate at the PE-LN 37,38 or PE-Mg:LN 39 interface. The previously described topographic feature at the PE-Mg:LN boundary for the Àz sample may obfuscate a full description of the conductivity in the vicinity of the boundary and requires further investigation.…”
mentioning
confidence: 99%
“…On the þz sample, photocurrents originating from charge accumulation were measured at the boundary between the PE area and Mg:LN for positive voltage (Figure 4(d)). Under these conditions, holes appear to accumulate at the PE-Mg:LN interface guided by electric fields across that boundary due to the spatial gradient of polarization charge, 37 facilitating spatially confined electron injection. The polarization dependent direction of the lateral electric field between the Mg:LN and PE areas can also be observed in the distribution of transient currents that are mediated by the accumulation of positive charge carriers at these boundaries (Figures 4(b) and 4(d)).…”
mentioning
confidence: 99%